THE REFERENCE SECTION OF THE LOWER-UPPER PERMIAN BOUNDARY BEDS IN THE VERKHOYANSK REGION AND ITS CORRELATION - Klets A.G.; Budnikov I.V.; Kutygin R.V.; Grinenko V.S. (My University, 2001)
The following Lower-Upper Permian brachiopod zonation is established in the Baraiy River basin (the western Verkhoyansk region): (1) the Megousia kuliki Zone bearing the associated Neouddenites-Tumaroceras yakutorum goniatite assemblage, (2) the Kolymaella ogonerensis Zone containing the Baraioceras-Tumaroceras kashirzevi ammonoid assemblage, (3) the Mongolosia russiensis Zone with the Daubichites-Sverdrupites harkeri ammonoid assemblage, (4) the Olgerdia zavodovskyi Zone, and (5) the Cancrinelloides obrutshevi Zone. The boundary between the Kungurian Stage of the Lower Permian and the Ufimian Stage of the Upper Permian is drawn at the base of the Kolymaella ogonerensis Zone of the Tumara Horizon. The most distinct biostratigraphic level is the base of the Mongolosia russiensis Zone, which corresponds to the lower Roadian boundary. The compatibility analysis of Permian biotic and abiotic events in the western Verkhoyansk region shows that the Mongolosia russiensis and Cancrinelloides obrutshevi zones correspond to phases of the highest sea level stand, which has determined ranges of the zones. The Baraiy River section can be accepted for the reference one in the Verkhoyansk region. It may also facilitate correlation of the Uralian and North American stage scales.
Keywords: Permian; Tumara Horizon; Delenzha Horizon; Kungurian Stage; Ufimian Stage; goniatites; brachiopods; Verkhoyansk region; Paleozoic::Permian; Палеозой::Пермская